Dissemination of researches in communication of selected universities in Metro Manila, Philippines - De Villa, Rhodora Ramonette Mendoza (2007.)
"This academe is not only tasked to educate but also to advance different fields of study, including communication, through researches. Part of these efforts is the need to share research findings to various pubics. Thus, this study aimed to analyze the manner by which researches in communication are disseminated in the top four universities in Metro Manila, Philippines. The study was exploratory in nature and it used the multiple-case (embedded) design. Interview schedules, questionnaires, and documents and records were used in data gathering. Purposeful sampling was employed in the selection of study units and key informants. From this sampling method, the following units were identified: the Department of Communication and the Ateneo Center for Communication Research and Training (CCRT) for the Ateneo de Manila; the Department of Communication Arts and Social Development Research Center (SDRC) at DLSU-Manila; the College of Mass Communication (CMC) and UP Center for Integrative and Development Studies (UP-CIDS) at UP Diliman, and the Department of Communication and Media Studies and Social Research Center (SRC) for UST. Data were analyzed using explanation-building. In general, the findings revealed that research was an important activity in the four academic units offering communication courses, research centers, and universities studied. This was mainly evidenced by the inclusion of the need to conduct researches in their vision, mission, or goals. However, not much emphasis was placed on research dissemination as an integral component in this endeavor."
Vita.
Thesis (M.A.) Communication Research)--University of the Philippines, Diliman.
Keywords: Communication -- Research -- Philippines -- Manila Metropolitan Area